Relevansi Kinerja Keuangan, Kualitas Laba, Intangible Asset, dengan Nilai Perusahaan - Gamayuni, Ridu Rika (Jurnal Trikonomika, 2012)
The purpose of this study is to empirically study 1) the difference between the book value of equity with the market value of equity, 2) the effect of financial performance (current ratio, ROA, debt to equity ratio, asset turnover), earning quality, and intangible asset on firm value, 3) This study also aim to prove whether earning quality as moderating variable on the relationship between financial performance and firm value. This research uses the sample companies registered between 2005-2009 on Indonesian Stock Exchange (IDX), they are included in the 50 leading companies in market capitalization . The result of this study using man whitney t-test, multiple regression, and moderated regression analysis finds that: 1) There are significant differences between the book value of equity with a market value of equity. Over the last three years (2007,2008,2009), the average equity market value is much higher than the book value of equity, 2) ROA (possitive and significant), debt to equity ratio (possitive and significant), intangible assets (possitive and significant) effected on firm value, but earning quality has not effected on firm value 3) Earning quality as a moderating variable has not proved affect the relationship between current ratio, ROA, debt to equity, asset turnover and firm value.